Arteriojejunal Fistula Presenting with Recurrent Obscure GI Hemorrhage in a Patient with a Failed Pancreas Allograft. (25th December 2013) - Desai, Nirmit; Patel, Sagar; Nwosu, Chinyere; Sung, Lok; Tack, Carl; Buscaglia, Jonathan M.; Nord, Edward P.; Wadhwa, Nand K.
Abstract : We present a case of a patient with a failed pancreaticoduodenal allograft with exocrine enteric-drainage who developed catastrophic gastrointestinal (GI) hemorrhage. Over the course of a week, she presented with recurrent GI bleeds of obscure etiology. Multiple esophago-gastro-duodenoscopic (EGD) and colonoscopic evaluations failed to reveal the source of the hemorrhage. A capsule endoscopy and a technetium-labeled red blood cells (RBC) imaging study were similarly unrevealing for source of bleeding. She subsequently developed hemorrhagic shock requiring emergent superior mesenteric arteriography. Run off images revealed an external iliac artery aneurysm with fistulization into the jejunum. Coiled embolization was attempted but abandoned because of hemodynamic instability. Deployment of a covered endovascular stent into the right external iliac artery over the fistula site resulted in immediate hemodynamic stabilization. A high index of suspicion for arterioenteric fistulae is needed for diagnosis of this uncommon but eminently treatable form of GI hemorrhage in this patient population.